2016
DOI: 10.1016/j.biortech.2016.06.078
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative lactic acid production from coffee pulp hydrolysate using Bacillus coagulans at laboratory and pilot scales

Abstract: In this study, the lignocellulosic residue coffee pulp was used as carbon source in fermentative l(+)-lactic acid production using Bacillus coagulans. After thermo-chemical treatment at 121°C for 30min in presence of 0.18molL(-1) H2SO4 and following an enzymatic digestion using Accellerase 1500 carbon-rich hydrolysates were obtained. Two different coffee pulp materials with comparable biomass composition were used, but sugar concentrations in hydrolysates showed variations. The primary sugars were (gL(-1)) glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 17 publications
1
54
3
2
Order By: Relevance
“…The final volume of the fermentation was 35.6 L (due to base addition) with a LA concentration of 58.7 g L −1 and, by the end of the downstream, the product was 1.06 L of a solution containing 930 g L −1 . Therefore, LA overall recovery yield was 45%, a value comparable to previous reports in the literature that used organic and agricultural residues [16,22]. In this case, most of the LA losses (about 60%) were the result of the micro-and nanofiltration steps.…”
Section: Lactic Acid Purificationsupporting
confidence: 81%
“…The final volume of the fermentation was 35.6 L (due to base addition) with a LA concentration of 58.7 g L −1 and, by the end of the downstream, the product was 1.06 L of a solution containing 930 g L −1 . Therefore, LA overall recovery yield was 45%, a value comparable to previous reports in the literature that used organic and agricultural residues [16,22]. In this case, most of the LA losses (about 60%) were the result of the micro-and nanofiltration steps.…”
Section: Lactic Acid Purificationsupporting
confidence: 81%
“…Various acids (organic and inorganic) have been proposed in the literature, such as sulphuric acid, hydrochloric acid, phosphoric acid, and citric acid, as efficient means for hemicellulose solubilisation [33]. Dilute sulphuric acid hydrolysis has been successfully employed in a variety of biomasses, including sugar beet pulp [34], coffee pulp and coffee mucilage [35,36] among others. The main disadvantage of this method is the production of inhibitory compounds (acetic acid, furfural, 5-hydrolxymethylfurfural (HMF)) that could hamper the fermentability of the produced hydrolysate.…”
Section: Pretreatment and Hydrolysis Conditionsmentioning
confidence: 99%
“…Companies like Galactic and NatureWorks have already included agricultural and food wastes in their production line [61]. Among the different renewable feedstocks proposed in the literature for LA production, such as municipal solid wastes [62], coffee byproducts [35,36] and food wastes [63][64][65], many researchers have also attempted to produce LA from DRB using various microbial strains.…”
Section: Production Of Lactic Acidmentioning
confidence: 99%
“…U.S. Department of Energy's National Laboratories have also identified lactic acid as one of the few promising platform chemicals that can be further converted to other important chemicals, such as acrylic acid, propylene glycol, acetaldehyde, and 2,3-pentanedione and polymers such as poly-lactic acid [3]. Bio-based lactic acid can be produced from different sources, including agricultural residues and food waste [4][5][6][7][8]. Lactic acid production using sugarcane bagasse feedstock showed that cellulose-based processes have larger lactic acid production rates and lower production costs than hemicellulose-based processes; and gypsum-free scenarios had the lowest production costs [9].…”
Section: Introductionmentioning
confidence: 99%